On being agents of change: A qualitative study of elective experiences of medical students at the Faculty of Health Sciences University of Cape Town South Africa - James Irlam; Lunelle Pienaar; Stephen Reid (African Journal of Health Professions Education, 2016)
Background. Student electives during the 5th year of the University of Cape Town (UCT) medical curriculum provide a 4-week work experience in the health system. The reflective reports of past students indicate that the electives may significantly shape their developing identities as health professionals and agents of change. Objective. To better understand how 5th-year medical elective students perceive themselves as agents of change to strengthen the elective programme in the Faculty of Health Sciences, UCT. The hypothesis was that the more choice that students are given over their learning, the greater is their sense of agency. Methods. Thirteen 5th-year student volunteers participated in four focus group discussions soon after completing their electives in district, regional or tertiary health facilities in the South African health system. Thematic analysis of the transcripts was performed independently by two of the authors. Results. Key themes were the importance of providing holistic patient-centred care, becoming a competent health professional, working within the health team and advocating for a better health system. The elective experience helped students to be more confident in their abilities and to better understand how to effect change at a clinical and health system level. Conclusion. This study supported the hypothesis that the more choice students have over their learning, the greater is their sense of agency. The electives are appreciated as opportunities to develop clinical skills and competencies and to better understand the role of future doctors within the health team and health system. The value of the UCT elective programme could be enhanced by greater promotion, funding for rural electives, and post-elective peer-to-peer feedback sessions. This study will inform planning for an extended 2016 medical elective programme in the Faculty.